Post COVID-19 precautions management in small-scale airports: Evaluation of check-in process in Erkilet airport by simulation - Elif Bolat; Savaş S. Ateş (Journal of Airline and Airport Management, 2020)
Purpose: The number of passengers, luggage, and cargo served at the airports increases at certain times due to flight density (peak hours). Due to the long queues at check-in desk during peak hours, there may be delays in flight operation processes. In addition, it is estimated that check-in queue times will increase even more in accordance with Covid-19 social distance rules.